2001
DOI: 10.1017/s0950268801005647
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carriage of antimicrobial resistant strains of Streptococcus pneumoniae in primary school children in Hong Kong

Abstract: SUMMARYA cross-sectional survey was conducted to determine prevalence and assess risk factors for carriage of antibiotic resistant strains of Streptococcus pneumoniae in healthy school children in Hong Kong. Throat swabs were collected from 1455 subjects and written questionnaires providing demographic data and medical history were completed by parents. The overall carriage rate of Streptococcus pneumoniae was 3n5 %, of which 49 % were penicillin resistant. High levels of resistance to tetracycline (73 %), ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…The relationship between the carriage of S. pneumonia and educational level is not clear. Although some studies showed a close relationship between low educational level of the parents and higher nasopharyngeal colonization [12], other studies [13, 27, 28] such this study failed to show this association. Although reported in some studies [12, 29-31], this study did not identify any associations between the carriage of S. pneumonia , smoking habits, breast feeding and recent antibiotic use.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The relationship between the carriage of S. pneumonia and educational level is not clear. Although some studies showed a close relationship between low educational level of the parents and higher nasopharyngeal colonization [12], other studies [13, 27, 28] such this study failed to show this association. Although reported in some studies [12, 29-31], this study did not identify any associations between the carriage of S. pneumonia , smoking habits, breast feeding and recent antibiotic use.…”
Section: Discussioncontrasting
confidence: 65%
“…Most NP pneumococcal carriage studies enrolled children [8] or younger children [9-12]. Several studies have included healthy children [13] whereas others included children with concomitant respiratory infection [11]. This study described the epidemiology of NP carriage of S. pneumonia .…”
Section: Discussionmentioning
confidence: 99%
“…Hong Kong has prevalence of resistant microbial strains consistently ranked amongst the highest worldwide [18][19][20][21][22][23][24][25][26][27] and increasing numbers of potent antibiotics reported to be ineffective. 6,24,27 We performed a cross-sectional study in this setting of highly prevalent antibiotics resistance to investigate the prevalence of antibiotics nonadherence and to assess the association between general knowledge of antibiotics and adherence.…”
mentioning
confidence: 99%
“…Two studies 23 , 28 reported that history of hospital admission within the past 3 months is a significant risk factor for AMR bacterial carriage with low heterogeneity [OR 3.43 (95% CI 2.13–5.51, I 2 = 0)]. The pooled results in our meta-analysis of five studies 18 , 20 , 23 , 29 , 30 reported that antibiotic use within the past 3 months among young children is a risk factor for carriage of AMR bacteria (penicillin non-susceptible S. pneumoniae , MRSA and ESBL-producing Enterobacteriaceae). The pooled estimate [OR 2.65 (95% CI 1.70–4.12)] shows that the results are significant.…”
Section: Resultsmentioning
confidence: 63%
“…Firstly, the difference in the locations and their distribution of study setting is one of the contributors to the variance. For example, one study 29 collected samples from children from primary schools situated in areas of older public housing and in new towns in Hong Kong while the other study 18 collected samples from children in 18 school districts distributed over the whole of Hong Kong. Another possible reason could be the difference in laboratory guidelines used in the studies.…”
Section: Discussionmentioning
confidence: 99%